2015
DOI: 10.1002/adfm.201503047
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Hydrogel Microencapsulation Inhibits Devitrification and Enables Large‐Volume Low‐CPA Cell Vitrification

Abstract: Cryopreservation of stem cells is important to meet their ever-increasing demand by the burgeoning cell-based medicine. The conventional slow freezing for stem cell cryopreservation suffers from inevitable cell injury associated with ice formation and the vitrification (i.e., no visible ice formation) approach is emerging as a new strategy for cell cryopreservation. A major challenge to cell vitrification is intracellular ice formation (IIF, a lethal event to cells) induced by devitrification (i.e., formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 55 publications
2
133
1
Order By: Relevance
“…For vitrification or low-CPA vitrification, cooling process is very simple compared to programmable slow freezing because the sample is directly immersed in liquid nitrogen for the fastest cooling available (Fahy, 1986b; Fahy et al, 1984; Huang et al, 2015; Wang et al, 2016) (Figure 1D (a)). Because no ice forms in either extra- or intracellular solution, no water or CPA transport across the cell membrane during freezing/thawing occurs (Fahy and Wowk, 2015) (Figure 1D (b).…”
Section: Fundamentals Of Cryopreservationmentioning
confidence: 99%
See 3 more Smart Citations
“…For vitrification or low-CPA vitrification, cooling process is very simple compared to programmable slow freezing because the sample is directly immersed in liquid nitrogen for the fastest cooling available (Fahy, 1986b; Fahy et al, 1984; Huang et al, 2015; Wang et al, 2016) (Figure 1D (a)). Because no ice forms in either extra- or intracellular solution, no water or CPA transport across the cell membrane during freezing/thawing occurs (Fahy and Wowk, 2015) (Figure 1D (b).…”
Section: Fundamentals Of Cryopreservationmentioning
confidence: 99%
“…Its extension form was further successfully used for the design of CPA equilibration for adherent endothelial cells (Davidson et al, 2015). Compared with programmed slow freezing, vitrification/low-CPA vitrification requires comparatively more CPA; therefore CPA addition and removal processes are more time consuming and costly (Choi et al, 2015a; Choi et al, 2015b; Huang et al, 2015; Wang et al, 2016). …”
Section: Fundamentals Of Cryopreservationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown promising protective effects of biomaterials on cell cryopreservation [80]. In a more mechanistic study, alginate hydrogel was shown to inhibit devitrification during the warming process of vitrified stem cells [81]. Altogether, these beneficial properties make encapsulation an encouraging strategy for cell therapy and the cryopreservation process.…”
Section: Challenges For Scale Up For Large Volume Cell Therapiesmentioning
confidence: 99%